Aratoi: Our Journeys to Aotearoa: Collaborative Knowledge Construction at a Regional Art Gallery in New Zealand. Issue 1 (1st July 2021) - McNaughton, Esther Helen
Abstract: How can regional art galleries support the development of cultural understanding in their communities? The 2019 collaborative project Aratoi: Our Journeys to Aotearoa between Nelson, New Zealand's Suter Art Gallery te Aratoi o Whakatū and eight local schools explored this question. Students' artworks were hung alongside the gallery's collection, enriching dialogue within the exhibition through the provision of voices otherwise absent. Building on the gallery's collection and history, this project demonstrated the evolution of the gallery's colonial roots into a broader discussion of culture. Participating teachers believed the project allowed public recognition of students' abilities and ideas; expression of a school community's special character; cross-curricular learning; cohesive whole school learning; bicultural learning; and pre-service teacher development. It also enabled meaningful exploration of Aotearoa New Zealand's histories.